Improved polarization and endurance in ferroelectric Hf0.5Zr0.5O2 films on SrTiO3(110). Issue 6 (28th January 2022) - Song, Tingfeng; Tan, Huan; Estandía, Saúl; Gàzquez, Jaume; Gich, Martí; Dix, Nico; Fina, Ignasi; Sánchez, Florencio
Abstract : With SrTiO3 (110) substrates, the ferroelectric polarization of Hf0.5 Zr0.5 O2 improved by 50%, with remanent polarization as high as 33 μC cm −2 in a film of less than 7 nm thickness. Abstract : The metastable orthorhombic phase of Hf0.5 Zr0.5 O2 (HZO) can be stabilized in thin films on La0.67 Sr0.33 MnO3 (LSMO) buffered (001)-oriented SrTiO3 (STO) by intriguing epitaxy that results in (111)-HZO oriented growth and robust ferroelectric properties. Here, we show that the orthorhombic phase can also be epitaxially stabilized on LSMO/STO(110), presenting the same out-of-plane (111) orientation but a different distribution of the in-plane crystalline domains. The remanent polarization of HZO films with a thickness of less than 7 nm on LSMO/STO(110) is 33 μC cm −3, which corresponds to a 50% improvement over equivalent films on LSMO/STO(001). Furthermore, HZO on LSMO/STO(110) presents higher endurance, switchable polarization is still observed up to 4 × 10 10 cycles, and retention of more than 10 years. These results demonstrate that tuning the epitaxial growth of ferroelectric HfO2, here using STO(110) substrates, allows the improvement of functional properties of relevance for memory applications.